(untitled) (Scientific journal of the Fergana State University, 2023)
Given that in the process of globalization in education, students are becoming more aware of the news through the media and social networks, it is advisable for the science teacher to regularly enrich the subject with news. The aim of the article is to be innovative as a method of constantly enriching the "Topic Development" with new information based on the principle of "Reading for Life". and the opportunity to work on their own. The content and quality of the teacher’s lessons will increase, the level of knowledge of students and the effectiveness of the educational process in the educational institution will rise to a higher level. The "theme development" is constantly improving due to scientific and technical innovations, the content is enriched and there is no end to it. As a result, the textbook "Topic Development" on the optional topic of the textbook is constantly improving and enriching the content, and this process continues uninterrupted, increasing the potential of the science teacher, the level of knowledge of students and the effectiveness of the educational process. The innovative source "Theme Development" prepared on the basis of this proposed method will serve as the main source of further improvement of the education